Sandal Upanat : Peran Kekayaan Intelektual Desain Industri dalam Mendorong Daya Saing Destinasi Pariwisata Borobudur ke Kancah Internasional - Yetti Rochadiningsih; Muhammad Affan Syahrul; Maria Sari Megaputri; Syauqy Ushma Haris (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Borobudur's cultural heritage as a global tourism destination requires innovative strategies in local product development. This research examines the role of Intellectual Property (IP) in the industrial design of Upanat Sandals in increasing the competitiveness of the Borobudur National Tourism Destination (DPN) and its surroundings in the international arena. Through a normative legal research method with a descriptive-analytical approach, the study focuses on analysing industrial design regulations, IP documentation, and in-depth interviews with industry players and tourism stakeholders. Specifically, the research investigates how the Upanat Sandal industrial design can be a strategic instrument in building the identity and competitiveness of tourism destinations. The results revealed that IP protection on Upanat Sandals has the potential to create tourism product differentiation, encourage creative economy innovation, and strengthen Borobudur destination branding at the international level. The findings show that the development and protection of industrial design IP can be an effective strategy in increasing tourist attractiveness, presenting the uniqueness of local culture, and opening up new economic opportunities. However, the research also identified significant challenges, such as low public awareness of the importance of IP protection and the complexity of registration procedures that hinder the development of maximum potential.